Аграрний сектор України: сучасний стан, проблеми та перспективи реформування галузі - Михайленко, Ольга Валеріївна; Хільченко, Ірина Юріївна (My University, 2019)
У статті розглянуто сучасний стан, проблеми та перспективи реформування аграрного сектору України, розглянуто основні результати діяльності, проаналізовано ряд негативних тенденцій, які перешкоджають ефективній діяльності аграрних підприємств, а саме: складність прогнозів ціни на паливо, інфляція, недосконала нормативно-законодавча база, нестабільна політична ситуація, корупція. Обґрунтовано позиції щодо перспективних напрямів розвитку агропродовольчого ринку, а саме: впровадження ринку землі, ліквідація «тіньового» ринку зерна, покращення логістики, розвиток органічного виробництва. Abstract. The modern state and the prospects of developing the agrarian sector of Ukraine are considered in the article, the basic results of activity are considered, the row of negative tendencies that prevent to effective activity of agrarian enterprises is analyses, namely: the quality of human resources in the countryside, unpredictability in the price of fuel, inflation, an imperfect regulatory and legislative framework, political instability, and corruption. Positions are reasonable in relation to the prospective directions of the development of agriculture, namely: land market implementation, liquidation of the "shadow" grain market, improvement of logistics, and the development of organic production. Purpose. Agriculture has been historically one of the main sectors of the Ukrainian economy. Considered for centuries as a "bread basket of Europe,” Ukraine today possesses arable land which equals 30% of the arable land of the European Union and 2.1% of the global arable land. But it has always been about quality, not quantity: Ukraine accounts for about 25% of the world most fertile black soil, which makes our country unique in terms of agricultural potential. Results. The priority directions of innovative development of the agrarian sector are: – increasing crop yields by using more efficient and effective technologies; – eeducing costs for the use of precision agricultural technology; – investing in additional production; – changing the process and depth of processing, shifting from export of agricultural products to the export of food products; – passing the necessary certification procedures to enter new markets; – improving the marketing of Ukrainian products. – creating and introducing into production highly productive varieties and hybrids of agricultural crops, new breeds of animals and poultry; – stimulating agro-ecological activity, developing alternative organic farming; – training high-quality professional staff. Conclusions. The Ukrainian agricultural sector has enormous potential and prerequisites for further growth, but there are problems and issues. Solving these problems will bring the level of agribusiness to the highest in the world. The approach to problem solving is complex: it requires solutions to problems both at the state level and at the level of agricultural producers. Agro-industrial production, as one of the main components of the Ukrainian economy, provides 15-20% of GDP in a stable way, despite all the existing problems in the industry. Therefore, the development of the agrarian sector is a significant area for the growth of the national economy as a whole and a means of solving various socio-economic and global challenges, especially when the country's economy is at the stage of overcoming the economic downturn.
Keywords: розвиток аграрного сектору; основні ринки збуту; обсяг аграрного експорту; ринок землі; експортні потоки; development agrarian to the sector; basic markets of sale; volume of agrarian export; land market; export flows; кафедра обліку і аудиту